Biochar reduces colloidal phosphorus in leachate by regulating phoD- and phoC-harboring microbial communities during drying/rewetting cycles - Xiaochun Wang; Hongnuo Ge; Yunying Fang; Chunlong Liu; Kamel M. Eltohamy; Zekai Wang; Xinqiang Liang (Biochar, 2023)
Abstract Drying and rewetting (DRW) events cause the release of colloidal phosphorus (Pcoll, 1–1000 nm) in leachate, and biochar is considered an effective inhibitor; however, the microbial mechanism remains elusive. In this study, three successive DRW cycles were performed on the soil columns to assess the effect of biochar addition on Pcoll content and its possible associates, including phosphatase-producing microbial populations (phoD- and phoC-harboring microbial communities) and alkaline/acid phosphatase (ALP/ACP) activities. Results showed that the biochar addition significantly decreased the Pcoll by 15.5–32.1% during three DRW cycles. The structural equation model (SEM) confirmed that biochar addition increased phoD- and phoC-harboring microbial communities and ALP/ACP activities, which reduces the release of Pcoll into leachate. In addition, the manure biochar was more effective than the straw biochar in promoting competition and cooperation in the co-occurrence network (2–5% nodes increased on average), and the key taxa Proteobacteria and Cyanobacteria were identified as the dominant species of potential ALP/ACP activities and Pcoll content. Our findings provide a novel understanding of biochar reducing Pcoll loss from the phosphatase perspective by regulating the phoD- and phoC-harboring communities during DRW events. Graphical abstract